PERAN PEMERINTAH DALAM MENCEGAH DAN MENANGANI PENURUNAN KASUS STUNTING DI KABUPATEN ACEH UTARA - Ana Zahara; Fidhia Aruni; Eka Chyntia (Sekolah Tinggi Ilmu Administrasi Nasional, 2023)
Handling stunting is one of the national development priorities listed in the 2020-2024 RPJMN with a target of reducing the stunting rate by 11.8% by 2024 (3). The main focus in handling stunting by the Indonesian Ministry of Health is providing specific nutritional interventions given in the First 1000 Days of Life (HPK). North Aceh Regency is ranked second in Aceh with a prevalence of stunted toddlers of 38.3%. Its position is followed by Pidie Jaya Regency with a prevalence of stunted toddlers at 37.8%. Regent Regulation Number 41 of 2020 concerning the Acceleration of Reducing Integrated Stunting is a guideline for handling and preventing stunting in North Aceh Regency. The presence of this regulation is expected to prevent stunting in North Aceh Regency. However, the presence of these regulations has so far not been able to reduce the stunting rate in North Aceh Regency. For this reason, through the Regent's Regulation, researchers want to see how the Government's efforts to collaborate with stakeholders in preventing and reducing the prevalence of stunting in children under five in North Aceh Regency based on Regent's Regulation Number 41 of 2020 Accelerating Integrated Stunting Reduction. This research also supports the MBKM Era research focus on the Health Independence Focus Area. The urgency of this research is to find out how the North Aceh Regency Government is making efforts to prevent and handle the prevalence of stunting in children under five in North Aceh Regency and to describe information on how the North Aceh District Government creates collaboration with all parties responsible for preventing and handling the prevalence of stunting in children under five in North Aceh Regency. This research uses descriptive qualitative research, and data is collected by interviewing and distributing Google forms to government officials, stakeholders and related communities. The output of this research is a national journal accredited 1-6 with the expected TKT level of 3.